IMPLEMENTASI PENDIDIKAN IN FORMAL DAN NON FORMAL DALAM PENDIDIKAN AGAMA ISLAM MENURUT BUYA HAMKA (TELAAH BUKU “LEMBAGA HIDUP”) - Dwi Restiana (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Family education is an informal education. In the family, children's education is directed in the framework of religious cultivation and forming religious chilren. A very important role in education in the family is the role of parents. In the formation of behaviors, attitudes and habits, the cultivation of values and other behaviors of family influences are very strong and direct. According to Hamka, morals of students can be said as a reflection of the moral form of society where they are residing. This is because the life of every member of society in the social community is a miniature of culture that will be seen and then emulated by every student. The existence of the community is a laboratory and a macro source full of alternatives to enrich the implementation of the educational process. And the main points of childhood education is the responsibility of parents and the community at home. Therefore, the authors review the book of Lembaga Hidup. Hamka explained the role of informal and non formal education with the concept and form of its implementation in Islamic education. The type of this research is Library Research which is part of Qualitative Research. Library research is used to solve the problem of conceptual-theoretical research, either about educational leaders or certain educational concepts. The data were obtained by searching for books compiled by Hamka. In interpreting the text contained in various writings of Hamka, researchers use Content Analysis Methods which is used to describe a specific analytical approach. Based on the data that have studied and analyzed, the results can be summarized as follows: 1) in the view of Hamka, education in schools can not be separated from home education. The first and foremost education, the family plays a leading role and holds the responsibility for the education of his children. Society is an educational institution that is very broad and influential in the process of forming a child's personality.2) the forms of informal education and non-formal education by Buya Hamka, the review of Lembaga Hidup book is to lay the foundations for the development of children such as childhood experience, ensuring the child's emotional life, inculcate the basis of moral education, providing the basis of social education , and laying the foundations of religion.